Apoptosis And Genotoxicity Of Selected Β-Carboline Compounds Against Chronic Myelogenous Leukemia Using In Vitro Experimental Models - Kamaruzaman, Nur Azzalia (2018)
β-carboline is known for its numerous traditional uses and has been widely investigated for various health indications. In particular, recently β-carboline has shown some promising findings in the field of anticancer. Hence this study investigates the potential anticancer activity of β-carboline compounds using in vitro models. Thirty synthesized β-carboline compounds were tested using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay for anticancer activity and selectivity index (SI) against four human cancer (colon HT-29, cervical HeLa, liver Hep G2 and leukemia K562) and two non-cancer (mouse embryo fibroblasts BALB/c3T3 and human foreskin fibroblasts Hs27) cell lines.